1994
DOI: 10.1246/cl.1994.905
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between CO2 and Electrochemically Reduced Species of N-propyl-4,4′-bipyridinium Cation

Abstract: The one-electron reduced species of N-propyl-4,4′-bipyridinium cation (1+) which is generated under electrolysis at −1.1 V vs. SCE was found to be able to react with CO2 although it is even a neutral radical. The intermediate CO2 adduct was furthermore reduced by one-electron at the same electrolysis potential to form a stable CO2 adduct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Although redox-active systems have yet to achieve industrial utility, they have the potential of producing a pure CO 2 stream even from dilute gas mixtures, such as air [141]. Among different classes of redox-active compounds that have been explored, such as bipyridines [142,143], disulfides [49] and copper/amine systems [29,30], the quinone species [141,[144][145][146] are of particular interest [40], owing their strong binding affinity for CO 2 in their reduced form compared to that of their neutral state [39,147]. Quinones are organic compounds derived from aromatics, through conversion of an even number of -CH= groups into -C(=O)-groups [148].…”
Section: Redox-active Carriers and Electrode Reactionsmentioning
confidence: 99%
“…Although redox-active systems have yet to achieve industrial utility, they have the potential of producing a pure CO 2 stream even from dilute gas mixtures, such as air [141]. Among different classes of redox-active compounds that have been explored, such as bipyridines [142,143], disulfides [49] and copper/amine systems [29,30], the quinone species [141,[144][145][146] are of particular interest [40], owing their strong binding affinity for CO 2 in their reduced form compared to that of their neutral state [39,147]. Quinones are organic compounds derived from aromatics, through conversion of an even number of -CH= groups into -C(=O)-groups [148].…”
Section: Redox-active Carriers and Electrode Reactionsmentioning
confidence: 99%
“…[1,15] In support of this conclusion, a distinct UV/Vis spectrum attributed to a carbamate species was collected during the electrochemical reduction of CO 2 in the presence of n-propyl-4,4'-bipydinium. [16] The temperature dependence of pyridinium-catalyzed CO 2 reduction was investigated for the temperature range (0-45 8C). The cathodic current, which followed an Arrhenius-like dependence, was observed to increase with increased temperature ( Figure 5).…”
mentioning
confidence: 99%
“…Thus, when the first reduction occurs in the presence of CO 2 , the capture reaction in equation 10 is followed rapidly by a second reduction [Eq. [5] They found that reduction of Prbipy + in the presence of CO 2 resulted in production of the species Prbipy-CO 2 À . (12)].…”
Section: àmentioning
confidence: 99%
“…Ishida et al. described a different type of adduct chemistry based on the formation of a strong nucleophile formed by reduction of the N ‐propyl‐4,4’‐bipyridinium cation, Prbipy + . They found that reduction of Prbipy + in the presence of CO 2 resulted in production of the species Prbipy‐CO 2 − .…”
Section: Introductionmentioning
confidence: 99%